Asymmetric Autonomy in a Human Rights Perspective - Sugianto, Bambang; Utami, Iftitah; Rusmini, Rusmini; Hartikasari, Juniar (Faculty of Law, Universitas Pekalongan, 2024)
Asymmetric autonomy is a phenomenon that gives rise to unique dynamics in the context of granting authority to autonomous regions. From a human rights perspective, this phenomenon raises deep questions about the balance between regional autonomy and the protection of individual rights. This research aims to explore the impact and implications of asymmetric autonomy on human rights. This research uses a document analysis approach and literature study to detail the mechanism of asymmetric autonomy and its impact on human rights. The results show that the implementation of asymmetric autonomy can provide significant benefits for local development, but also poses potential risks to individual rights. There is a tension between the regional autonomy granted and the need to protect basic rights. Furthermore, this research highlights the need for a clear regulatory framework and effective oversight mechanisms to maintain this balance. The discussion also includes efforts that can be taken by the government and stakeholders to mitigate the risk of human rights violations in the context of asymmetric autonomy. This research contributes to our understanding of the complexity of the relationship between asymmetric autonomy and human rights. The policy implications resulting from this research can help governments and policy makers in designing regulatory frameworks that support regional development without compromising individual rights.Keywords: Asymmetric Autonomy; Human Rights; Impact; Balance; Regulation